Magnetic order, spin dynamics and transport properties of the pyrochlore iridate Y2Ir2O7 - Liu, Hui; Tong, Wei; Ling, Langsheng; Zhang, Shile; Zhang, Ranran; Zhang, Lei; Pi, Li; Zhang, Changjin; Zhang, Yuheng (Solid state communications, 2014)
In the present paper, we report the bulk magnetization, electron-spin-resonance spectra and transport properties of Y2Ir2O7. It is found that Y2Ir2O7 exhibits a magnetic transition at Tc=150K and coexistence of antiferromagnetic and ferromagnetic component due to geometrical frustration. The antiferromagnetic order is due to Ir–O–Ir superexchange interactions and the ferromagnetic component is caused by canting of the moments from the antiferromagnetic state. The behavior of spin dynamics confirms that antiferromagnetic ordering with all-in/all-out structure is responsible for the existence of ferromagnetic component. The resistivity reveals that this compound is a semiconductor and the variable-range hopping process dominates the transport mechanism. •Y2Ir2O7 exhibits coexistence of antiferromagnetic and ferromagnetic component due to geometrical frustration.•AFM ordering with all-in/all-out structure is responsible for the existence of FM component.•This compound is a semiconductor and the variable-range hopping process dominates the transport mechanism in the range of the whole temperature measured.